2022
DOI: 10.1103/physrevb.105.205124
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical correlations in single-layer CrI3

Abstract: Chromium triiodide is an intrinsically magnetic van der Waals material down to the single-layer limit. Here, we provide a first-principles description of finite-temperature magnetic and spectral properties of monolayer (ML) CrI 3 based on fully charge self-consistent density functional theory (DFT) combined with dynamical mean-field theory, revealing a formation of local moments on Cr from strong local Coulomb interactions. We show that the presence of local dynamical correlations leads to a modification of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…However, in recent days, DMFT has been proven to be a reliable and well-controlled approximation to study correlation effects in bulk solids as well as for two-dimensional systems 42 . Recent studies on 2D or layered materials reported that DFT + DMFT technique describes the electronic and magnetic properties more accurately than DFT + U or standard DFT [43][44][45] .…”
Section: Effective Hubbard Parametersmentioning
confidence: 99%
“…However, in recent days, DMFT has been proven to be a reliable and well-controlled approximation to study correlation effects in bulk solids as well as for two-dimensional systems 42 . Recent studies on 2D or layered materials reported that DFT + DMFT technique describes the electronic and magnetic properties more accurately than DFT + U or standard DFT [43][44][45] .…”
Section: Effective Hubbard Parametersmentioning
confidence: 99%
“…By decreasing U from 0.5 to 0 eV, we observe a bandgap reduction of 140 meV, qualitatively comparable to the experimental value of bandgap reduction achieved by ramping V g from −40 to +40 V (Δ n = 4.02 × 10 12 cm –2 ). We thus conclude that the large bandgap renormalization observed here is mainly attributed to the gate-induced electron doping of CrBr 3 , causing a decrease of U due to the enhanced screening of Coulomb interactions. , …”
Section: Resultsmentioning
confidence: 48%
“…Instead, we performed selected calculations using a hybrid functional (PBE0 [ 57 ]), a strategy that often provides a very favorable description of quasiparticle energies [ 58 ] and which has been considered preferable over DFT + U calculations [ 59 ]. In fact, in certain materials, the DFT + U approach has been found to deviate further from DFT plus dynamic mean-field theory calculations than pure, semilocal DFT [ 60 ].…”
Section: Methodsmentioning
confidence: 99%